Evaluation of Systemic Immune-Inflammation Index for Predicting Mortality in Sepsis Patients - Faisal Muchtar; Haizah Nurdin; Syamsul Hilal Salam; Andi Husni Tanra; Ari Santri Palinrungi; A.M. Irsyad Sulkifli Mangga Barani (Faculty of Medicine, Hasanuddin University., 2025)
Introduction: This study aims to measure the accuracy of Systemic Immune-Inflammation Index (SII) in predicting 28-day mortality in sepsis patients in intensive care unit. Methods: This study was conducted as a retrospective cohort study. The study was conducted in the intensive care unit of Dr. Wahidin Sudirohusodo General Hospital. The study subjects consisted of all sepsis patients admitted to the intensive care unit during the period January 2023 to December 2023 who met the inclusion criteria. Results: Total sample is 147 participants. Systemic Immune-Inflammation Index (SII) showed a significant difference in predicting sepsis mortality. SII has an AUC value of 0.763 with a sensitivity of 69.6% and a specificity of 71.1% at a cut-off of 2003.395. Conclusions: Systemic Immune-Inflammation Index (SII) scores are associated with increased mortality in sepsis patients in the intensive care unit of Dr. Wahidin Sudirohusodo Hospital. The SII can be a prediction tool in clinical practice in predicting mortality of sepsis patients.